2022
DOI: 10.3390/nu14030582
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverage Consumption in Adults: Evidence from a National Health Survey in Peru

Abstract: High consumption of sugar-sweetened beverages (SSB) is associated with a high risk of non-communicable diseases. Evidence of SSB consumption is needed to inform SSB-related policies, especially in countries with a high consumption, such as Peru. Using data from Peru’s National Health Survey conducted in 2017–2018, the consumption of homemade and ready-to-drink SSB was estimated from a single 24 h dietary recall, accounting for socio-demographic and health-related variables. Regression models were fitted to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…While mean purchases of high-sugar taxed beverages were more homogenous than purchases of untaxed beverages, the Andean highlands and the southern coast purchased the largest volume of high-sugar taxed beverages. This partially aligns with results of a prior study of SSB consumption using national data, which found that consumption of homemade SSBs was the highest in the Andean highlands, while the highest mean consumption of ready-to-drink SSBs occurred in the southern and central coasts [ 10 ]. In this study, the southern coast had the highest proportion of high SES households outside of Lima, which may have contributed to the larger volume of high-sugar beverage purchases.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While mean purchases of high-sugar taxed beverages were more homogenous than purchases of untaxed beverages, the Andean highlands and the southern coast purchased the largest volume of high-sugar taxed beverages. This partially aligns with results of a prior study of SSB consumption using national data, which found that consumption of homemade SSBs was the highest in the Andean highlands, while the highest mean consumption of ready-to-drink SSBs occurred in the southern and central coasts [ 10 ]. In this study, the southern coast had the highest proportion of high SES households outside of Lima, which may have contributed to the larger volume of high-sugar beverage purchases.…”
Section: Discussionsupporting
confidence: 89%
“…Prior research in urban populations has also shown an inverse relationship between Dietary Quality Score and SES in Peru [ 31 ]. On the other hand, a study of ready-to-drink and homemade SSB consumption found that individuals who completed secondary school (the middle education category) consumed greater quantities of both types of SSBs than those with less education, but had no statistically significant differences in consumption of either beverage type from the higher education group [ 10 ]. Taken together, this suggests that households with higher SES and education currently consume more unhealthy products, although this may be changing as Peru progresses through the obesity transition [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, we provided the first evidence of the agreement between the 2019 WHO CVD risk laboratory-based and non-laboratory-based models; furthermore, we leveraged on a nationally representative survey conducted in a LMIC. 26 Different CVD risk equations have been created but none has proved to produce reliable estimates for LMICs. The 2019 WHO CVD risk charts were adapted for LMICs using extensive datasets for its derivation, recalibration and validation, which brings them several advantages over previous risk charts.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, we provided the first evidence of the agreement between the 2019 WHO CVD risk laboratory-based and non-laboratory-based models; furthermore, we leveraged on a nationally representative survey conducted in a LMIC 26. Different CVD risk equations have been created but none has proved to produce reliable estimates for LMICs.…”
Section: Discussionmentioning
confidence: 99%